FLUXING AGENT FOR ELECTROSLAG SURFACING OF BIMETALLIC WORM WHEELS - E. I. Marukovich; V. A. Zemtsov; D. A. Meshkov; I. O. Sazonenko (Литьë и металлургия)
Electric schemes of replacement of slag bath at electroslag process with application of solid and ring electrodes are viewed. Flux fo r production of bimetal castings out of cast-iron — tin bronze has been developed.